Divergence of the fermentative and bromatological characteristics of 25 sorghum hybrid silages - Silva,Thiago Carvalho da (2012)
The objective of this study was to evaluate the divergence of bromatological and fermentative characteristics of silages of 25 sorghum (Sorghum bicolor L. Moench) hybrids. The experimental design was completely randomized with 25 treatments and four replications. The mean values of pH differed with variation from 3.45 to 3.87 for hybrids 866005 and 870051, respectively, and the mean pH value was 3.66. The average percentage of lactic acid ranged from 2.90 to 7.43 dag/kg of dry matter (DM) in hybrids 870035 and 866005, respectively, with an average of 4.65 dag/kg DM. Through cluster analysis by the Tocher method and average Euclidean distance based on the fermentative characteristics, five groups were formed: one with 18 hybrids, another with four and three groups with one hybrid in each. In group three, there were the hybrids that showed the highest values of lactic acid. Hybrids 870025, 870035, 870081, 870095, 866034, and 870031 showed higher DM content and the hybrid BRS 610 had the lowest average compared with the others. Hybrids 1F305, BRS 610, Volumax, and XBS60329 had the lowest levels of non-fiber carbohydrates and higher neutral detergent fiber corrected for ash and protein. Despite the fermentative and bromatological divergences between hybrids, they are not a limiting factor to silage production.